Association between either vaginal and cesarean section delivery with cervical cancer and precursors - Fernández, Luis (2015)
OBJETIVE: To determine whether there is a greater relationship between women with vaginal delivery than women conparto caesarean presentation of squamous cervical cancer and its precursors. DESIGN: Case-control study conducted at Regional Hospital of Trujillo, Peru. MATERIAL AND METHODS: It was considered as cases 177 women with clinical and histopathological diagnosis of cervical cancer and its precursors met in 2000 to 2012. Controls were constituted by 179 women without a diagnosis of cervical cancer treated at the same hospital and who they had had vaginal or caesarean deliveries excclusivamente. To determine which characteristics are associated with cervical cancer multivariate analysis was applied, taking as predictors age, parity, mode of delivery and age of first intercourse. Then, a logistic regression analysis was performed to determine which variables constitute risk factors. For each of the variables studied the odds ratio was calculated. Statistical significance was calculated with the chi square test. RESULTS: Of the variables analyzed, the age of first intercourse l, the paragravidez and the type of delivery variable significantly associated with the occurrence of cervix (OR 1.1; 1.2: 24.1, respectively) cancer. The category of vaginal delivery was a risk of more than 24 times, compared with cesarean delivery (OR 24, 1, 1, P <0.000008). CONCLUSION: Our results suggest that among the variables associated with cervical cancer, vaginal delivery is the most heavily aociado and predisposes women to develop this cancer and its precursors.